2012
DOI: 10.20460/jgsm.2012615782
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Organizational Justice on Turnover Intention: Evidence From an International Electronic Chain Store Operating in Turkey

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…Among different kinds of justice, interactional justice (p = 0.00, r = -0.38) and procedural justice (p = 0.00, r = -0.36) had a significant negative correlation with Turnover intention. A similar correlation has been also found by Iyigun and Tamer’s study ( 34 ). Additionally, the significant negative relation between interactional justice and Turnover intention is congruent with the studies of Hassani et al ( 16 ), Parker et al ( 35 ) and Jones et al ( 36 ), but inconsistent with the results of Aryee ( 25 ) and Nadiri & Tanova ( 37 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among different kinds of justice, interactional justice (p = 0.00, r = -0.38) and procedural justice (p = 0.00, r = -0.36) had a significant negative correlation with Turnover intention. A similar correlation has been also found by Iyigun and Tamer’s study ( 34 ). Additionally, the significant negative relation between interactional justice and Turnover intention is congruent with the studies of Hassani et al ( 16 ), Parker et al ( 35 ) and Jones et al ( 36 ), but inconsistent with the results of Aryee ( 25 ) and Nadiri & Tanova ( 37 ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the results of the statistical tests indicated a significant negative correlation (p < 0.001, r = -0.36) between organizational justice and Turnover intention, which have been corroborated by other studies ( 13 - 19 , 29 , 31 - 34 ). This represents that employees’ appropriate conceptions of justice in an organization make the basis for their satisfactions and positive states of mind.…”
Section: Discussionsupporting
confidence: 84%
“…Managers should pay particular attention to justice and create a positive mentality in their employees to ensure their satisfaction and stability in their organizations. Iyigun and Tamer (2012) found that education, tenure and married status were all favorable and significantly associated with TI, while negative and significant relationships between TI with distributive justice and procedural justice. Moreover, OJ affects workers' perceptions of fairness.…”
Section: Organizational Justice and Turnover Intentionmentioning
confidence: 91%
“…This idea is supported by the results presented in the literature. Iyigun and Tamer [45] as well as Phayoonpu and Mat [85] showed the negative and statistically significant association between procedural justice and turnover intention. Also, in research conducted by Kwai et al [57] procedural justice proved to be an important factor that increased organizational commitment and decreased turnover intention.…”
Section: H5mentioning
confidence: 99%